2022
DOI: 10.3390/nu14020258
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean Diet and Fatty Liver Risk in a Population of Overweight Older Italians: A Propensity Score-Matched Case-Cohort Study

Abstract: Hepatic steatosis, often known as fatty liver, is the most common hepatic disease in Western countries. The latest guidelines for the treatment of nonalcoholic fatty liver disease emphasize lifestyle measures, such as changing unhealthy eating patterns. Using a propensity score-matching approach, this study investigated the effect of adhering to a Mediterranean diet (MedDiet) on fatty liver risk in an older population (≥65 years) from Southern Italy. We recruited 1.403 subjects (53.6% men, ≥65 years) who compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 66 publications
0
1
0
Order By: Relevance
“…Although there are some diets useful to achieve these therapeutic goals (DASH diet, ketogenic diet, intermittent fasting diet) [ 85 ], Med-Diet plays a role in prevention of hepatic steatosis [ 94 ]. For instance, the high content of PUFAs could reduce insulin resistance and intrahepatic triglyceride content, thereby improving NAFLD [ 92 ].…”
Section: Effects Of Med-diet On Mets Components and Nafldmentioning
confidence: 99%
“…Although there are some diets useful to achieve these therapeutic goals (DASH diet, ketogenic diet, intermittent fasting diet) [ 85 ], Med-Diet plays a role in prevention of hepatic steatosis [ 94 ]. For instance, the high content of PUFAs could reduce insulin resistance and intrahepatic triglyceride content, thereby improving NAFLD [ 92 ].…”
Section: Effects Of Med-diet On Mets Components and Nafldmentioning
confidence: 99%
“…Interestingly, while lowering the relative risk (RR) of all-cause mortality, consuming alcohol with food, it did not have an association with the risk of liver cirrhosis. In this study, it was also shown, that daily alcohol intake was associated with a higher liver cirrhosis risk with no further distinguishment regarding type of alcoholic drink [42]. Results of a recently published analysis focusing on the Mediterranean diet and fatty liver risk in overweight older Italians revealed that individuals with a fatty liver index > 60 had a higher intake of wine [43] and consumed alcohol at a higher percentage over an extended period of time.…”
Section: Alcoholic Beverages and The Liver: The Impact Of Spirits Win...mentioning
confidence: 48%
“…Indeed, in this study, it was reported that a 1 L increase in spirits consumption is associated with a 35.2% increase in cirrhosis mortality rate. Results of a recent prospective cohort study of UK Biobank participants excluding abstainers and individuals with previous cancers, liver cirrhosis, and stroke as well as myocardial infarcts suggested that spirit drinking as well as beer and cider drinkers were at higher risk of liver cirrhosis (spirits: HR 1.48; 95% CI 1.08-2.03; beer/cider: 1.36; 95% CI 1.06-1.74) compared to red wine drinkers after adjusting for the average weekly alcohol consumption [42]. Interestingly, while lowering the relative risk (RR) of all-cause mortality, consuming alcohol with food, it did not have an association with the risk of liver cirrhosis.…”
Section: Alcoholic Beverages and The Liver: The Impact Of Spirits Win...mentioning
confidence: 99%
“…In our study, there were no statistically significant differences between all four groups regarding weight and body mass index. Regarding fatty liver, overweight and the importance of the role of body mass index (BMI) have been demonstrated in many studies (35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%